2013
DOI: 10.3892/mmr.2013.1425
|View full text |Cite
|
Sign up to set email alerts
|

Growth and expression of rat bone marrow mesenchymal stem cells modified by nerve growth factor in diabetic rat bladders

Abstract: The aim of the present study was to determine whether rat bone marrow mesenchymal stem cells (MSCs) transfected with the nerve growth factor (NGF) gene and then transplanted into diabetic rat bladder tissues survive and continue to express NGF. A recombinant lentiviral vector carrying the NGF gene was constructed and transfected into rat bone marrow MSCs. BrdU‑labeled immunohistochemistry was used to observe NGF expression in the transfected MSCs. BrdU‑labeled and NGF‑transfected MSCs were transplanted into di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…NGF is significant in the nociception of adult injured tissues, and the altered gene expression induced by NGF may have an influence on the phenotypic alteration [11]. It has been found that NGF plays a key role in the reduction of diabetic neuropathy morbidity, thus exogenous NGF might contribute to the diabetic neuropathy treatment [12]. BDNF participates in the plasticity and development of peripheral nervous system (PNS) as well as central nervous system (CNS), as it affects not only differentiation and proliferation but also synaptic activity and neurotransmission [13].…”
Section: Introductionmentioning
confidence: 99%
“…NGF is significant in the nociception of adult injured tissues, and the altered gene expression induced by NGF may have an influence on the phenotypic alteration [11]. It has been found that NGF plays a key role in the reduction of diabetic neuropathy morbidity, thus exogenous NGF might contribute to the diabetic neuropathy treatment [12]. BDNF participates in the plasticity and development of peripheral nervous system (PNS) as well as central nervous system (CNS), as it affects not only differentiation and proliferation but also synaptic activity and neurotransmission [13].…”
Section: Introductionmentioning
confidence: 99%
“…Significant increases in micro-vessel density and bladder regeneration were noted in the experimental group, compared with the control group. In another study, bone marrow MSCs transfected with the nerve grow factor (NGF) gene survived and continued to express NGF in diabetic rat bladder tissues 4 weeks following implantation [75]. …”
Section: Gene and Stem Cell Therapymentioning
confidence: 99%